Application Of UCAR® Chill Kote? Lining To Ilmenite Smelting - C. Coetzee; P. H. Lamont; D. Bessinger; J. Rabe; J. Zietsman; J. Muller (The Southern African Institute of Mining and Metallurgy, 2007)
The UCAR® CHILL-KOTE? freeze lining concept combines wall cooling with carbon and graphite refractories of higher thermal conductivities to ?chill? the refractory lining by transferring heat from the refractory lining. Effective sidewall water cooling, together with the efficiency of the heat dissipating conductive refractories, lowers the temperature of the lining to below that of the molten process materials. This causes a layer of slag and process metal to solidify or ?freeze? and form a protective ?skull? which completely coats the refractory hot face. Once formed, the slag skull insulates the refractories, reducing heat loss and protect the lining from erosion, chemical attack, thermal shock, and other stresses. The result: extended life and greatly improved refractory performance. The Ilmenite smelting process depends on the presence of a solidified slag skull to protect sidewall refractory material from chemical attach by molten slag. No known refractory material is able to withstand this corrosive material. To date, UCAR has not applied their Chill Kote ? technology in the ilmenite smelting industry. This paper revolves around the results obtained from conducting an ilmenite smelting campaign on a 500kW DC open-arc furnace with a UCAR designed refractory system. The purpose of this test was to establish the effects such a lining has on refractory wear and the reduction-smelting process. Proper thermo-couple management enabled the authors to monitor lining wear for the duration of the campaign. Prior to the pilot-scale campaign, modeling work was completed to evaluate the feasibility of applying UCAR® CHILL-KOTE? technology to ilmenite smelting furnaces. The successful operation of a pilot-scale furnace equipped with the UCAR® CHILL-KOTE? lining as well as concise modeling suggest that it should be a viable option to consider for an industrial-scale furnace.